2013
DOI: 10.5194/bg-10-7279-2013
|View full text |Cite
|
Sign up to set email alerts
|

Finding immune gene expression differences induced by marine bacterial pathogens in the Deep-sea hydrothermal vent mussel <i>Bathymodiolus azoricus</i>

Abstract: Abstract. The deep-sea hydrothermal vent mussel Bathymodiolus azoricus lives in a natural environment characterised by extreme conditions of hydrostatic pressure, temperature, pH, high concentrations of heavy metals, methane and hydrogen sulphide. The deep-sea vent biological systems represent thus the opportunity to study and provide new insights into the basic physiological principles that govern the defense mechanisms in vent animals and to understand how they cope with microbial infections. Hence, the impo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…found that after being challenged by Vibrio spp., fewer immune‐related genes were upregulated in deep‐sea mussels (Martins et al., ). Expressions of some immune genes are even inhibited after infection (Martins, Queiroz, Santos, & Bettencourt, ), and the repression of complementary systems has been shown to be required for maintaining symbiosis in other marine invertebrates (Poole et al., ). Similar results were also observed in B. azoricus : in the absence of symbionts, lysozyme expression was upregulated, and declined after re‐acquisition of bacteria (Detree et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…found that after being challenged by Vibrio spp., fewer immune‐related genes were upregulated in deep‐sea mussels (Martins et al., ). Expressions of some immune genes are even inhibited after infection (Martins, Queiroz, Santos, & Bettencourt, ), and the repression of complementary systems has been shown to be required for maintaining symbiosis in other marine invertebrates (Poole et al., ). Similar results were also observed in B. azoricus : in the absence of symbionts, lysozyme expression was upregulated, and declined after re‐acquisition of bacteria (Detree et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting evolution can generate genetic variation in gene expression that is constitutive or inducible (e.g. G*E interactions) and generates variation in resistance and hostpathogen specificity (Rosenblum et al 2009;Bahlool et al 2013;Martins et al 2013;Barribeau et al 2014). However, purely plastic differences can also be strong because many of these immune traits are also regulated by host condition, prior exposure to pathogens, or are directly manipulated by parasites for their own benefit.…”
Section: Introductionmentioning
confidence: 99%
“…These studies concluded that the immune gene transcriptional activity was modulated at two levels, i.e., over the course of time and according to the bacterial strain tested, suggesting thus, a selective response toward Vibrio spp. when vent mussels were experimentally challenged during 24 h [53,54]. Additional experiments were carried out with Vibrio diabolicus aiming at the analysis of gene expression differences between distinct vent mussel populations from the hydrothermal vent sites Menez Gwen (MG, 800 m depth) and Lucky Strike (LS, 1700 m depth) both located on the Mid-Atlantic region, near the Azores islands.…”
Section: Posttranscriptomics Studies In Bathymodiolus Azoricusmentioning
confidence: 99%
“…Furthermore, these studies have allowed analyses using immune challenged mussels comparatively to acclimatized control mussels, maintained under aquarium conditions. In view of our previous experiments performed with live gill tissues and postcapture immune gene expression studies in B. azoricus acclimatized to atmospheric pressure, the presence of endosymbiont bacteria is now being under investigation as a driving factor under which host-immune genes may transcriptionally be modulated and reciprocally endosymbiont genes may transcriptionally be modulated by the host [53][54][55][56]. Moreover, the impact of aquarium acclimatization on B. azoricus immune responses and its capacity to react to V. diabolicus challenges was recently evaluated during recurrent incubations with V. diabolicus during short periods of time, followed by clean sea water incubations allowing animals to depurate and subsequently be reexposed to the same load of V. diabolicus over a period of 3 weeks acclimatization experiment [74].…”
Section: Host-endosymbiont Interactions: Implications For Host Immunimentioning
confidence: 99%